(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Pistacia lentiscus essential oil has been shown to have antidepressant like effect, gastro-protective effect. Objectives This study aims to evaluate for the first time the toxicological profiles and neurobehavioral effects of Pistacia lentiscus (PLEO) in single or triple administration using several animal models. Furthermore, the possible mechanisms of action involved in antidepressant like effects were investigated. Methods To this end, mice were randomly divided into the negative control group, treated groups (12.5; 25 and 50mg/kg of PLEO), positive control groups (Diazepam 2 mg/kg; Fluoxetine 10 mg/kg; Omeprazole 25 mg/kg). Concerning the toxicological profile, animals were treated daily for 28 days with PLEO or vehicle, and at the end of the experiment, mice were assessed in a battery of tests. Then, were sacrificed by cervical dislocation for histopathological examinations and estimation of biochemical parameters. Results Our outcomes demonstrate that, single administration of PLEO induced a potential anxiolytic like effect. However, triple administration of PLEO provokes a stronger antidepressant like effect more than single administration; this effect was reversed when mice were pretreated with yohimbine, olanzapine, and cyproheptadine. Daily treatment with PLEO has no significantly effect on body weight. Histopathological examination of target organs has not any tissue alterations; in addition, biochemical parameters of treated groups are within normal ranges in comparison to the negative control. Regarding locomotor and exploratory behavior, daily treatment with PLEO has no effect on muscular tone. It is also demonstrate that administration 3 times per day possesses a strong gastro-protective effect. Conclusion The findings of this investigation revealed for the first time that, PLEO essential oil possesses a potential anxiolytic and antidepressant like effects. It was also demonstrated that PLEO does not modify exploratory and locomotor activity. The pretreatment with PLEO prevents gastric ulcers. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 188-201